Respuesta :

Answer:

- 1 and 1

Step-by-step explanation:

using the rule of exponents

• [tex]a^{0}[/tex] = 1

- ([tex]2^{0}[/tex]) = - 1

( - [tex]\frac{4}{9}[/tex])^0 = 1


For this case we have that by definition, any number raised to zero gives 1.

Knowing that:

[tex]\frac {a ^ 2} {a ^ 2} = 1[/tex] and by power properties of the same base we have that: [tex]\frac {a ^ 2} {a ^ 2} = a ^ {2-2} = a ^ 0[/tex]

So:

[tex]a ^ 0 = 1[/tex]

So, if we have:

[tex]- (2) ^ 0 = - (1) = - 1\\(- \frac {4} {9}) ^ 0 = 1[/tex]

Answer:

[tex]- (2) ^ 0 = - (1) = - 1\\(- \frac {4} {9}) ^ 0 = 1[/tex]


ACCESS MORE